Pemanfaatan Tanaman Obat Keluarga (TOGA) sebagai Alternatif Pengobatan Mandiri Nyeri Sendi - Faridah Faridah; Adi Saputra Junaidi; Putra Hadi (Jurnal Abdimas Kesehatan (JAK), 2023)
Family Medicinal Plant (TOGA) or often also called living pharmacies are selected types of plants that are efficacious as medicines that are cultivated for family needs for medicines so that the principle of independence in family medicine will be realized. Family herbal medicine that is safe because it rarely causes side effects, is easy to process and consume for first aid for minor ailments such as fever, cough, overcoming inflammation of joints and bones or helping to maintain stamina. The existence of. TOGA in the home environment is very important. The purpose of this service is to provide counseling regarding the use of TOGA as an alternative to self-medication and to provide information about arthritis that can be treated using TOGA to the community of RT 13, Selamat Telanaipura Village, Jambi City. The method used in this service is to provide counseling and provide TOGA tree seeds for planting. The target partners are groups of housewives in RT 13, Selamat Telanaipura Village, Jambi City. The results of developing activities in R13 can increase the motivation of housewives to make more use of TOGA as a treatment, increase public knowledge about arthritis and natural ingredients that can be used to reduce arthritis pain